Device-related complications in subcutaneous versus transvenous ICD: a secondary analysis of the PRAETORIAN trial - Knops, Reinoud E.; Pepplinkhuizen, Shari; Delnoy, Peter Paul H M; Boersma, Lucas V A; Kuschyk, Jürgen; El-Chami, Mikhael F; Bonnemeier, Hendrik; Behr, Elijah R; Brouwer, Tom F; Kaab, Stefan; Mittal, Suneet; Quast, Anne-Floor B E; et al. (European heart journal, 2022)
The subcutaneous implantable cardioverter-defibrillator (S-ICD) is developed to overcome lead-related complications and systemic infections, inherent to transvenous ICD (TV-ICD) therapy. The PRAETORIAN trial demonstrated that the S-ICD is non-inferior to the TV-ICD with regard to the combined primary endpoint of inappropriate shocks and complications. This prespecified secondary analysis evaluates all complications in the PRAETORIAN trial.The PRAETORIAN trial is an international, multicentre, randomized trial in which 849 patients with an indication for ICD therapy were randomized to receive an S- ICD (N = 426) or TV-ICD (N = 423) and followed for a median of 49 months. Endpoints were device-related complications, lead-related complications, systemic infections, and the need for invasive interventions. Thirty-six device-related complications occurred in 31 patients in the S-ICD group of which bleedings were the most frequent. In the TV-ICD group, 49 complications occurred in 44 patients of which lead dysfunction was most frequent (HR: 0.69; P = 0.11). In both groups, half of all complications were within 30 days after implantation. Lead-related complications and systemic infections occurred significantly less in the S-ICD group compared with the TV-ICD group (P < 0.001, P = 0.03, respectively). Significantly more complications required invasive interventions in the TV-ICD group compared with the S-ICD group (8.3% vs. 4.3%, HR: 0.59; P = 0.047).This secondary analysis shows that lead-related complications and systemic infections are more prevalent in the TV-ICD group compared with the S-ICD group. In addition, complications in the TV-ICD group were more severe as they required significantly more invasive interventions. This data contributes to shared decision-making in clinical practice.